The Tenacity of The Prophet’s Companions: A Historical Study of Their Noble Characters - Usman Jimoh Muhammad; Muhammad Yahaya (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This paper explores the origin of Islam as a divine religion revealed to the Prophet Muhammad (peace be upon him) and conveyed to mankind. The demise of the prophet, however, did not bring an end to the message of Islam. It was as a result of the tenacity of his companions, who were able to completely comprehend the message, preserve the teachings, and entrust them to the next generation. The life chronicle of the companions unveils how they sacrificed their noble status, life, and wealth for the cause of Islam. Their practical application of the teachings of the religion, such as their tenacity in upholding the spirit of truthfulness and trustworthiness, embracing the love for the prophet and his family, promoting the spirit of brotherhood, and ensuring swift compliance with his instructions, is noteworthy. This paper equally looks into their commitment to preserving and disseminating the message of Islam, and how they promoted harmonious Muslim non-Muslim relations, following the dictates of the Quran and the teachings of the prophet. The research adopted a library method to explore related materials from various library collections. In conclusion, this study disclosed the dedication of the prophet’s companions as a means through which God aims to ensure the continuity of the message of Islam for future generations. In addition, their exemplary life inspires Muslims to follow in their footsteps in promoting the path of Islam.